The effect of fatigue on the cognitive status and quality of life of patients with Lyme- borreliosis - T. Yu. Malysh; M.A. Trishchynska (Клінічна та профілактична медицина, 2023)
The relevance of the issue of asthenic disorders is determined by a high prevalence among patients with various chronic pathologies and its impact on the disease course, treatment efficacy, and quality of life. The purpose of the study was to analyze the dependence of cognitive disorders and the quality of life of patients with Lyme borreliosis on the level of fatigue.